Ocena przedsięwzięć informatycznych w małych i średnich przedsiębiorstwach - Dyczkowski, Mirosław (The evaluation of IT projects in small and medium enterprises, 2006)
The paper presents the results of the research done by the author, which were intended to make a preliminary recognition of the IT project practices in small and medium enterprises (SME). The researches have been done from the perspective of the SME, where the IT projects have been implemented. The data acquired, partially presented in this article, has proved the quite good evaluation of the projects which mostly do not overrun time and cost limits, meet functional objectives as well as utility and quality requirements.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1134, s. 245-255